2021
DOI: 10.26442/00403660.2021.01.200551
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapy for acute respiratory infections caused by influenza viruses: current possibilities

Abstract: Routinely the influenza virus significantly contributes to the formation of the annual incidence of acute respiratory infections, with a peak in winter season. The high level of mutagenic potential of influenza viruses is a standard factor determining the complexity of the rational choice of pharmacotherapy. The upcoming epidemiological season 20202021 brings additional challenges for health care practitioners mediated by the widespread prevalence in the human population of a new infection caused by the SARS-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 86 publications
0
1
0
Order By: Relevance
“…Favipiravir is a prodrug that converts to an active metabolite with broad-spectrum activity developed to treat influenza and used against Ebola (9,10). Published clinical trials on the adult population reported benefits in patients diagnosed with COVID-19 (11); however, the data were not conclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Favipiravir is a prodrug that converts to an active metabolite with broad-spectrum activity developed to treat influenza and used against Ebola (9,10). Published clinical trials on the adult population reported benefits in patients diagnosed with COVID-19 (11); however, the data were not conclusive.…”
Section: Introductionmentioning
confidence: 99%